2020
DOI: 10.5114/jcb.2020.101688
|View full text |Cite
|
Sign up to set email alerts
|

Focal low-dose-rate prostate brachytherapy for low- and intermediate-risk prostate cancer

Abstract: Purpose: To prospectively investigate the efficacy and feasibility of focal low-dose-rate (LDR) prostate brachytherapy for low-and intermediate-risk prostate cancer.Material and methods: Between October 2014 and May 2019, nineteen low-and intermediate-risk prostate cancer patients who presented with abnormality on both diffusion-weighted and T2-weighted magnetic resonance imaging (MRI) underwent focal LDR brachytherapy at our institution. Focal gross tumor volume (F-GTV) was delineated on transrectal ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This objective was met in 16 of 17 patients, however, the mean focal GTV size was only 0.7 cc, compared to 3.8 cc in our study. A planning objective of V100% ≥98% to the focal volume has also been used previously (17,19). The post-implant dosimetry and size of the focal target volume reported in our study is comparable to that reported by Cosset et al (15), Mahdavi et al (17) and Kunogi et al (19) (Table 1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This objective was met in 16 of 17 patients, however, the mean focal GTV size was only 0.7 cc, compared to 3.8 cc in our study. A planning objective of V100% ≥98% to the focal volume has also been used previously (17,19). The post-implant dosimetry and size of the focal target volume reported in our study is comparable to that reported by Cosset et al (15), Mahdavi et al (17) and Kunogi et al (19) (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…Despite the increasing uptake of focal therapy for PCa across the globe, including LDR brachytherapy, robust evidence to support its efficacy and optimal utilisation is still maturing and further studies are urgently required (13). Data specifically for lesion-targeted focal LDR brachytherapy is particularly lacking, with only six small studies (total of 115 patients) published to date (Table 1) (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…It is a standard treatment method within the framework of clinical trials. The effectiveness and safety of focal LDR BT are well-studied and described in the scientific literature 37 38…”
Section: Methods and Analysismentioning
confidence: 99%